Ostrannenie : on "strangeness" and the moving image : the history, reception, and relevance of a concept - Oever, Annie van den, 1957- (Key debates, 2010)
Defamiliarisation or ostrannenie, the artistic technique of forcing the audience to see common things in an unfamiliar or strange way, in order to enhance perception of the familiar, ihas become one of the central concept of modern artistic practice, ranging over movements including Dada, postmodernism, epic theatre, and science fiction, as well as our response to arts. Coined by the Soviet literary critic Victor Shklovskii in 1917, ostrannenie has come to resonate deeply in film studies, where it entered into dialogue with the French philosopher Derrida's concept of differance, bordering on 'differing' and 'deferring'. Striking, provocative and incisive, the essays of the distinguished film scholars in this volume recall the range and depth of a concept that since 1917 changed the trajectory of theoretical inquiry.